Improving Operational Efficiency in Digital Printing Services Through a Web-Based Information System: An Empirical Case Study - Rusmin Saragih; Eka Pandu Cynthia; Maulidania Mediawati Cynthia (Journal of Information Technology and Systems Engineering, 2026)
The increasing demand for efficiency and accuracy in service industries has encouraged the adoption of digital technologies, particularly in small and medium-sized enterprises (SMEs) such as printing services. However, many organizations still rely on manual or semi-digital processes, leading to inefficiencies, data inconsistencies, and communication gaps across operational units. This study aims to improve operational efficiency in digital printing services through the design and implementation of a web-based information system. A qualitative case study approach was employed at CV. Raskha Media Group, with data collected through observation, interviews, and documentation. The system was developed using the Waterfall model and modeled with Unified Modeling Language (UML) to ensure structured development. The implementation integrates order management, inventory control, payment processing, and production workflows into a unified platform. System evaluation was conducted using Black Box and White Box testing, as well as ISO/IEC 25010 and System Usability Scale (SUS). The results show a 100% functional success rate, a SUS score of 74.1 indicating good usability, and an overall quality score of 89%, reflecting high system performance. These findings demonstrate that the proposed system effectively reduces operational errors, enhances inter-departmental communication, and improves overall efficiency. This study contributes to the advancement of information systems research by providing empirical evidence of the role of integrated web-based systems in supporting digital transformation and business process optimization in service-oriented SMEs.